Effect of heat treatment on erosion-corrosion - Ahmad Syazwan, Yahya (2012)
Erosion-corrosion is complex phenomenon which involves the interaction between mechanical process of solid particle erosion and electrochemical process of corrosion. This thesis is investigates the effect of heat treatment on erosion-corrosion. The aims of this project are to investigate the effect of heat treatment on erosion-corrosion of stainless steel in aqueous slurries. Specimens of AISI Type 301 Stainless Steel been annealed heat treated to 1070 °C with slowly cooling type. Two types of specimens which are annealed and control specimens of AISI Type 301 Stainless Steel were prepared to evaluate the erosion-corrosion affected. Erosion-corrosion test then were carried out by immersing those specimens in aqueous 3.5% NaCl solution and presence of 10% sand particles. Velocity, temperature and concentration in aqueous were stated as fixes as we maintain to focus the effect of heat treatment. Erosion-corrosion test undergo specifically was electrochemical test and Potentiostat was choosing as the tools to analyzed corrosion potential rate. Annealed AISI Type 301 Stainless Steel show increased in corrosion rate (mmpy) than control AISI Type 301 Stainless Steel due to decreasing of steel hardness (HRC) after being annealed.